Pendampingan Parenting Islami dalam Pembentukan Karakter Islami Anak Usia Dini bersama Mata Hati Care Centre di PAUD Wildani Dk. Bladeg Ds. Kutukan Kec. Randublatung Kab. Blora - Hidayah , Luthfi; Siswadi, Siswadi; Rofiq, Ainur (Keris: Journal of Community Engagement, 2024)
The problem of children is now growing, such as homeless children and beggars, the cases of smoking toddler, child injuries due to fighting, sexual abuse, exploitation, even to trafficking. Children now spend more time in front of television, computer or gadget, rather than to communicating with parents or play that involves physical activities. Meanwhile, the demands of life are increasingly high, many parents are forgetting its primary role as educators for their children, and they are busy working outside the home to make ends meet.Consequently, the responsibility of parents to form children's character are often overlooked. In addition, parents are now more emphasized that children have to excel academically than build their character. The lack of discussion between parents and children results in a lack of communication and attention, so that some children experience a crisis of morals and Islamic values ​​that are inherent in them. So it is necessary to have an Islamic parenting forum that covers this so that we understand each other. Islamic parenting is a parenting method for children as a solution to educational methods with an approach to the character of morality and the religiosity of the Islamic religion. The principles of parenting related to character development, these principles include self-exemplary, togetherness with children in realizing moral values, democratic attitudes, openness, honesty in children, as well as unity of words and actions that give birth to trust and authority. High trust and authority will bring up children's appreciation of parents, having the impact of the emergence of self-discipline values ​​originating from the child's conscience.